2012
DOI: 10.4025/actascianimsci.v34i2.10895
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and crude protein fractions of Coastcross grass under grazing on winter, spring and summer in Southern Brazil - doi: 10.4025/actascianimsci.v34i2.10895

Abstract: ABSTRACT. The objective of this study work was to assess crude protein fractions in structural components (leaves, stem and dead material) of Coastcross grass (Cynodon dactylon (L.) Pers) under grazing, on winter, spring and summer seasons, in the Northwestern of Paraná, South of Brazil. Were determined CP, NDF, ADF contents and protein fractions, A, B1, B2, B3 and C. The analysis of CP showed great differences among months, but there was no difference among seasons. NDF and ADF in the stem were lower (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
12
1
1
Order By: Relevance
“…High leaf participation values are desirable, as they usually present higher crude protein and lower neutral detergent fiber contents than stems (Branco et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High leaf participation values are desirable, as they usually present higher crude protein and lower neutral detergent fiber contents than stems (Branco et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Grasses of the genus Cynodon, such as Coastcross-1, have been widely used in tropical and subtropical regions to feed ruminants and horses, both as pasture form and as conserved forage, especially hay (Branco et al, 2012). Due to their response to fertilization, these grasses are usually grown using high amounts of chemical fertilizers, especially nitrogen fertilizers (Corrêa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Shannak et al [1] , Zhoa and Cao [16] (n = 30, R 2 =0.90, P<0.0001) and Westreicher-Kristen et al [17] similar to our findings, they reported that in situ rumen undegradable protein (1-EPD) obtained from nylon bag method may be the reliable and accurately predicted from CP fractions based on CNCPS. Zhoa and Cao [14] indicated that the regression equations could be used as a possible alternative, when rumen cannulated sheep or cattle are not available in some laboratories.…”
Section: The Estimation Of Effective Protein Degradability (Epd)mentioning
confidence: 99%
“…So far, no single methods has been accepted as being reliably accurate for predicting the rumen CP degradation. In recent years, the CNCPS as an alternative for estimation of degradable protein has become widely accepted in the studies [12][13][14] , because CNCPS can be applied at the farm level and CP fractions could be measured easily in most feed analyses laboratories [15] . Morever, some researchers stated that in situ rumen degradability may be reliably and accurately predicted from CNCPS parameters [1,16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Pers.) has been highlighted for its elevated forage potential, response to fertilization, great adaptability to diverse environments, and flexibility of use as pasture, hay, and silage (Branco et al, 2012).…”
Section: Introductionmentioning
confidence: 99%